The Effect of Joint Hypermobility Syndrome on DOMS and Recovery Time - Nicole F Ostuni; Charles A Marinello; Taras Luzhnyy; Alexa Pawlikowski; Connor Vlasaty; Georgios Thomatos; Peter C Douris (International Journal of Sports Physical Therapy)
# Background